2020
DOI: 10.3348/kjr.2019.0567
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Dynamic Contrast-Enhanced Breast MRI: Lesion Conspicuity and Size Assessment according to Background Parenchymal Enhancement

Abstract: Breast ultrafast dynamic contrast-enhanced (DCE)-MRI takes multiple images before the first post-contrast phase of conventional DCE-MRI (1-13). High spatiotemporal resolution can be achieved with the use of various

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Honda et al found that BPE was lower on the twelfth and twentieth phases of a 75 s ultrafast protocol compared to the first post-contrast phase of conventional dynamic contrast-enhanced MRI, with higher lesion detectability at the ultrafast protocol time points in patients with higher BPE at the conventional MRI time point [36]. Other studies have also demonstrated higher lesion conspicuity in cases with moderate or marked BPE [37,38].…”
Section: Bpe On Emerging Mri Protocolsmentioning
confidence: 98%
“…Honda et al found that BPE was lower on the twelfth and twentieth phases of a 75 s ultrafast protocol compared to the first post-contrast phase of conventional dynamic contrast-enhanced MRI, with higher lesion detectability at the ultrafast protocol time points in patients with higher BPE at the conventional MRI time point [36]. Other studies have also demonstrated higher lesion conspicuity in cases with moderate or marked BPE [37,38].…”
Section: Bpe On Emerging Mri Protocolsmentioning
confidence: 98%
“…Ultrafast MRI is a contrast material-based technique that leverages radiology.rsna.org n Radiology: Volume 000: Number 0-Month 2021 a high-temporal-resolution sequence (,10 seconds) performed within the first 1-2 minutes after contrast material administration. Qualitatively, ultrafast techniques may help visualize important nonmass enhancement that differentiates DCIS from benign background parenchymal enhancement (70). Some quantitative metrics, including time to enhancement and maximum slope, have promise for improving MRI specificity (71,72).…”
Section: Mri Examinationmentioning
confidence: 99%
“…Another study also concluded that UF-DCE MRI could improve lesion conspicuity compared to conventional DCE-MRI, especially in women with premenopausal status and moderate-to-marked BPE. 8 In practice, reviewing maximum intensity projection (MIP) images of several time frames from UF-DCE MRI is a quick way of finding the target lesions ( Fig. 4 ).…”
Section: How To Interpret Uf-dce Mrimentioning
confidence: 99%
“…For example, UF-DCE MRI is useful in identifying hypervascular lesions when the background parenchymal enhancement (BPE) is marked, often observed in young women. 7 , 8 On the other hand, there may be differences caused by the variation in image acquisition protocols. In order to clarify the value of UF-DCE MRI in the care of breast cancer patients, these variables should be clarified.…”
Section: Introductionmentioning
confidence: 99%